"Let Us Pick the Organization": Understanding Adult Student Perceptions of Service-Learning Practice - Susan C. Reed; Howard Rosing; Helen Rosenberg; Anne Statham (The University of Alabama, 2022)
Service learning offers a pedagogy by which adult students are guided toward understanding their potential for leadership in civic life and community development, strengthening the impact that universities have in communities. In this study, qualitative data is analyzed to determine how adult students perceive their service-learning experiences and what the university could do to involve them more in the future. Respondents provide some evidence that they value opportunities to give back to communities where they have a connection; appreciate hands-on learning that is integrated with classroom learning; benefit from placement experiences that build upon prior knowledge and skills; and prefer greater choice in the selection of their service-learning placement. As the number of adult students entering higher education continues to rise and their retention remains a challenge, understanding how these students are engaged by service learning becomes an important area of exploration for post-secondary institutions.